From “water rights” to “right to water”: The legal framing of Modatima’s rights - Ramirez Perez, Diego Alonso (Revista de Estudios de la Justicia, 2024)
This study examines the legal framing of water conflicts in Chile, focusing on the social movement Modatima (Movement for the Defense of Water, Land, and Environmental Protection) and its interactions with the judicial system. Employing qualitative content analysis of 278 Modatima documents and 510 Court Rulings from 2011 to 2023, we analyze how the concepts of water and rights are framed by both Modatima and the judiciary. The research reveals three distinct legal framings of water: the neoliberal framing of the Court of Appeals, the human rights framing of the Supreme Court, and Modatima’s democratic framing. Our findings indicate that Modatima’s democratic legal framing emerges from the application of human rights principles to their specific context, resulting in a conceptualization of water as a public common good and proposing new rights related to water access, land-water connections, and health. This framing challenges existing legal interpretations and contributes to the democratization of water governance. The study demonstrates how social movements can reshape legal interpretations and democratic processes in resource management and environmental rights. It highlights the complex interplay between social movements, judicial decision-making, and the evolution of water rights discourse in Chile. These findings contribute to our understanding of the role of social movements in shaping adaptive water governance and offer insights into the potential for innovative approaches to water conflicts in the context of climate change challenges.